PENGARUH KOMPETENSI BAHASA INGGRIS TERHADAP KINERJA PEGAWAI - Putu Shinta Novianty; Eka Ayu Purnama Lestari; Komang Trisnadewi (Universitas Warmadewa, 2022)
Many opinions say that English competency is the basic asset to become qualified human resources. The aim of this study to determine how much influence English competency has on employee performance. This is a descriptive study with qualitative and quantitative approaches. The research subjects were the alumni of STMIK STIKOM Indonesia who had worked in the IT field. Some steps taken of this study include planning, data collection, data analysis, and data presentation. Planning is done by formulating questions in the form of a questionnaire. Furthermore, at the data collection stage, the questionnaire was distributed online to STMIK STIKOM alumni. The data obtained is in the form of answers to the questionnaire and then analyzed. The analysis process through several stages includes reading as a whole, classifying, then giving an explanation. The final stage is to present it in the form of a report. As a result, English competency has a significant effect on employee performance. This indicates that the effect of competence on employee performance is 67.0%. Regarding language competence, listening is the most often skill most used by Information Technology employees.